Peran Kegiatan Muhadoroh dalam Membentuk Kepercayaan Diri Siswa SDIT Widya Cendekia - Hayati, Firda; Salsabila, Ayesha Malika; Ramadhani, Adinda Putri; Shofa, Zakiyatus; Saputri, Esti Ayu; Safitri, Lia; Ramadhanti, Shandrina Angelica; Najihah, Ita Fatihatun; Mahfudoh, Tia; Kamilah, Yasmin Arum Rizkya; Tussolihah, Umda (IBTIDA-Jurnal Kajian Pendidikan Dasar, 2025)
This study was conducted to determine how muhadhoroh activities can help improve students' self-confidence at SDIT Widya Cendekia. This activity is a public speaking exercise that has become a regular part of the school program. Through muhadhoroh, students learn to speak in front of their peers, express their opinions, and develop courage from an early age. The study used a qualitative approach with interviews with four teachers directly involved. The data obtained were then analyzed to determine the role of teachers and the impact of the activities on students. The results showed that muhadhoroh had a positive influence on students' self-confidence, especially for those who were initially shy. Students became more confident speaking, had the courage to speak in front of the class, and were able to express their opinions more clearly. The support of teachers and parents also significantly contributed to students' feeling of preparedness and confidence. Overall, muhadhoroh activities can be an effective habit-forming tool for fostering self-confidence and developing positive character traits in elementary school students.